Dispersi Padat Asam Usnat dengan Teknik Freeze Drying menggunakan Poloxamer 188 sebagai Polimer - Deni Noviza; Lili Fitriani; Riana Zikra Fauzi (Fakultas Farmasi Universitas Andalas, 2018)
This study aimed to improve the solution of usnic acid, a poorly soluble drug using solid dispersions (SDs). The SDs were prepared by a freeze-drying technique with poloxamer 188 as a polymer. The physicochemical properties of the SDs were characterized using X-ray diffractometry (XRD) and Fourier transform-infrared (FT-IR) spectroscopy, Scanning Electron Microscopy (SEM),. In addition, drug content, solution test and dissolution profile was evaluated by using usnic acid (pure drug) and physical mixture as a reference. The results from XRD and SEM showed that usnic acid was molecularly dispersed in the SDs as an amorphous form. The FT-IR results suggested that intermolecular hydrogen bonding had formed between usnic acid and its carriers. The result of solubility test showed that solubility of solid dispersions 1:1; 1:2; 2:1 (5.80 µg/ml; 6.94 µg/ml ; 4.88 µg/ml) were higher than the physical mixture 1:1 ( 0.39 µg/mL) and pure asam usnat have the lowest solubility (0.34 µg/mL). In conclusion, SDs prepared by a freeze-drying technique used poloxamer as a polymer can be used to enhance solubility of usnic acid